The Influence of Service Quality, Product Quality, and Trust on Customer Satisfaction in Mortgage Financing Product: Empirical Study From Bank BTN Syariah KCP Probolinggo, Indonesia - Qomariyah, Munawarotul; Susila, Ahdiyat Agus; Aqidah, Waqi’atul (Golden Ratio of Data in Summary, 2025)
Using a quantitative approach, this study examines how customer satisfaction with KPR financing products at BTN Syariah KCP Probolinggo is impacted by service quality, product quality, and trust. Information was gathered through documentation, questionnaires given to 81 respondents, and observation. The findings indicated that all three independent variables significantly and favorably affected customer satisfaction simultaneously and partially. This is evidenced by the calculated F value greater than the F table and the significance value less than 0.05. Moreover, the t-test indicates an important impact of each factor on customer satisfaction. The coefficient of determination test shows that 47.2% of customer satisfaction is influenced by service quality, product quality, and trust, while other factors outside this study influence 52.8%. These findings indicate that improving service quality, product innovation, and building strong trust can increase customer satisfaction. Therefore, BTN Syariah KCP Probolinggo is advised to continue developing strategies to improve these three aspects to strengthen customer loyalty and competitiveness in the Islamic banking sector.